Progress in cumulative risk assessment of human health from combined exposure to environmental pollutants - CHENG Xiaomeng; ZHANG Yan; GAO Yu; TIAN Ying (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2024)
The combined exposure to environmental pollutants can result in unanticipated adverse effects on human health, and how to compare and assess these effects has always been a matter of great concern for the international community. Currently, several prevalent methods for assessing combined exposure risks in the field of human health risk assessment primarily encompass the hazard index (HI) method, the point of departure index (PODI) method, the margin of exposure (MOE) method, and the relative potency factor (RPF) method. The review summarizes the application of these methods to the cumulative risk assessment of combined exposure to the same class of chemicals with the same toxic mechanism, primarily focusing on pesticides such as organophosphorus pesticides, pyrethroids, carbamates, and neonicotinoids, as well as typical compounds intimately related to human production and life, including organophosphorus flame retardants, per- and poly-fluoroalkyl substances, and bisphenols. Furthermore, progress in the application of physiologically based pharmacokinetics models to human health risk assessment has been introduced, which might provide more options for risk assessment of combined exposure to multiple chemicals, and help to provide insights for further exploration and establishment of more systematic and scientific approaches to human health risk assessment.